2016
DOI: 10.1109/tsp.2016.2531628
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Time Reversal for Testing Granger Causality

Abstract: Abstract-Inferring causal interactions from observed data is a challenging problem, especially in the presence of measurement noise. To alleviate the problem of spurious causality, Haufe et al. (2013) proposed to contrast measures of information flow obtained on the original data against the same measures obtained on time-reversed data. They show that this procedure, time-reversed Granger causality (TRGC), robustly rejects causal interpretations on mixtures of independent signals. While promising results have … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(107 citation statements)
references
References 41 publications
7
100
0
Order By: Relevance
“…In addition, there was strong crosstalk between the left and right anterior prefrontal areas (BA 10L and BA 10R), particularly in the top-down SSVEP condition. All of these directed functional connectivity measures were reliably confirmed by additional observations using time-reversed data4546 (see the Supplementary information). However, neither the intermediate nor the bottom-up SSVEP conditions showed true directed functional connectivity because their time-reversal results in Granger causality were not significantly different from those of the original data, which is indicative of spurious causal relations, such as a volume conduction effect4546.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…In addition, there was strong crosstalk between the left and right anterior prefrontal areas (BA 10L and BA 10R), particularly in the top-down SSVEP condition. All of these directed functional connectivity measures were reliably confirmed by additional observations using time-reversed data4546 (see the Supplementary information). However, neither the intermediate nor the bottom-up SSVEP conditions showed true directed functional connectivity because their time-reversal results in Granger causality were not significantly different from those of the original data, which is indicative of spurious causal relations, such as a volume conduction effect4546.…”
Section: Resultssupporting
confidence: 57%
“…Statistical assessment of the connectivity was performed using the surrogate approach (1000 surrogates, p  < 0.05). In order to avoid spurious causal relations, we conducted the same Granger causality analysis using time-reversed data4546. That is, the reversed temporal order of all data points in the same EEG dataset was used to double-check the robustness of the inferred Granger-causal connectivity measures.…”
Section: Methodsmentioning
confidence: 99%
“…Next, we computed frequencyresolved Granger causality (GC) to quantify directed rhythmic neuronal interactions between brain areas for language that are known to be anatomically connected (9)(10)(11). Because the interpretation of connectivity estimated from neuromagnetic recordings is highly confounded by spatial leakage of source activity (12), we statistically compared, across the sample of 102 participants, the estimated GC with an estimate of GC after time reversal of the signals (13). This allowed us to conservatively discard a substantial subset of the predefined connections for which the direction and/or the strength of the estimated Granger causal interaction is likely Significance The brain's remarkable capacity for language requires bidirectional interactions between functionally specialized brain regions.…”
Section: Resultsmentioning
confidence: 99%
“…Haufe et al [67] have shown in a simulation study (sensor space) that conventional Granger causality analysis and surrogate testing by phase shuffling, might not be as effective as measures such as phase-slope index (PSI) [68], [69]. Haufe et al have also proposed an time-reversed scheme for Granger causality analyses and have shown that this improves the results and makes it as good as PSI performance [67], [70]. A later study by Vinck et al demonstrated that correlated and uncorrelated noise might have different effects on the causality analysis results [57].…”
Section: Discussionmentioning
confidence: 99%